Process-Induced Effects on Dielectric Constant of Injection Molded and Cast Film Liquid Crystalline Polymer - Shooter, Mark. (2017)
Abstract: Liquid Crystalline Polymers (LCPs) provide favorable dielectric properties for extremely high frequency (30 - 100 GHz) radio frequency device packaging and printed circuit board substrates. This investigation sought to determine the cause of process-induced effects in the dielectric constant between injection molded and cast film extruded LCP. Processing LCPs creates through-thickness hierarchical structure, consisting of a core and skin layer. Volume fraction of skin layer was determined to be responsible for the difference in dielectric constant between injection molding and cast film extrusion. Dielectric constant is a function of this volume fraction with a near linear relationship. Is was discovered that dielectric constant can be predicted by fundamental rule of mixtures, or adaptations from Lichtenecker, Maxwell-Garnett, and Jayasundere-Smith. All studied models predicted dielectric constant of cast films (100 - 200 µm) and injection molded plaques (1.60 mm) within a margin of error of ± 2 and 4 %, respectively, against experimental results.; Thesis (M.S.)--Tufts University, 2016.; Submitted to the Dept. of Mechanical Engineering.; Advisors: Michael Zimmerman, and Anil Saigal.; Committee: Michael Zimmerman, Anil Saigal, and Meredith Dunbar.; Keywords: Mechanical engineering, Polymer chemistry, and Electrical engineering.